СЕЛЕНИТЫ И СЕЛЕНАТЫ: СИСТЕМЫ SE-S-Н2О, РB-SE-S-Н2О, U-SE-Н2О И U-SE-I-Н2О - ТЕРМОДИНАМИЧЕСКИЙ АНАЛИЗ И ГЕОЛОГИЧЕСКИЕ ПРИЛОЖЕНИЯ - Кривовичев В.Г.; Депмайер В. (My University, 2005)
Due to the toxicity of selenium it is quite essential to analyze the conditions under which selenites and selc-nates replace selenides in the oxidation zones of sulfide ore deposits and upon weathering of technologic waste. Actually there are about 300 minerals known which contain significant amounts of sulfate, but only three sulfi-te-bearing mineral species. Selenium similar to sulfur, may occur as native element, but selenites arc the main form of its occurrence (20 mineral species); compounds of selenium in its highest oxidation state - selenates are rather rare - only three rare mineral are known: olsacherite, schmiederite and carlosruizite. Each of these three minerals contains two anionic groups: selenate and sulfate (schmiederite), selenate and selenite (olsacherite), and selenate and iodate (carlosruizite). For another supposed selenate - «kerstenite» - there are practically no data on its nature, are or even on its mere existence. Some anthydrous selenites with additional anions are known as products of volcanic fumaroles (the Great Tolbachic eruption, Kamchatka). Other selenites and selenates are for-med by chemical weathering of sulfides and selenides by oxygenated water under cinditions of high Eh and low pH (due to seasonal fluctuations of temperatures and atmospheric pressure). It is the purpose of this work to con-sider the manner of occurrence and the behavior of selenium during oxidation of selenides or selenium-bearing sulfide minerals and during formation of uranium deposits in sandstones. This purpose is performed by summari-zing in Eh-pH diagrams the results of calculations of equilibrium, and considering geologic occurrences. Ana-lysis of Eh-pH stability was carried out for clausthalite and molibdomenite, for uranil-selenites (derriksite, mar-thozite, piretite, guilleminite, demesmaekerite) and for carlosruizite in order to interpret the conditions of forma-tion of these minerals and to compare their geologic stabilities in low-temperature ore deposits. The absence of «kerstenite» (PbSeO4), even in mineral associations of high selenium content, may be understood by examinati-on of its stability with respect to anglesite when excess sulfur is present. VK gratefully acknowledges a DFG (Mercator - Gastprofessoren-Program) grant for support for the work.
Keywords: 49.747(01)